Search for heavy Majorana or Dirac neutrinos and right-handed W gauge bosons in final states with charged leptons and jets in pp collisions at $$\sqrt{s}=13$$ s=13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2024)
Springer Open.